Quality Standardization of Clotropis procera Leaves - Bhaskar, V.H.; Ajay, S.S. (Asian Journal of Chemistry, 2010)
Calotropis procera leaves were collected from forest area of Ghaziabad, India and identified as per WHO guidelines.